"Magnetism‐Optogenetic" System for Wireless and Highly Sensitive Neuromodulation. Issue 3 (2nd December 2021) - Tian, Yu; Zhang, Yingying; Zhang, Xinyu; Pan, Huizhuo; Zhang, Lili; Liu, Shuang; Chen, Yulan; Su, Lin; Zhao, Peiqi; Chang, Jin; Wang, Hanjie
Abstract: Neuromodulation is becoming more and more important in studying brain function, disease treatment, and brain–computer interfaces. However, traditional regulation methods cannot effectively achieve both wireless regulation and highly sensitive response, which are essential factors in neuromodulation. In this paper, a "magnetism‐optogenetic" system is constructed, which uses a magnetic field to drive mechanoluminescent materials (ZnS:Cu) to generate light, thus stimulating photogenetic proteins. This system effectively combines the wireless magnetic regulation with the high sensitivity of optogenetics. The results show that the luminous intensity of this system changes with the power of an external magnetic field. In addition, under the continuous stimulation of the wireless magnetic field, this system can activate hippocampal‐related neural responses and induce the expression of C‐fos. In the end, this system can further regulate the movement behavior of rats with C1V1 protein expression in the primary motor cortex. This new magnetism‐optogenetic system will provide an excellent reference for wireless and highly sensitive neuromodulation. Abstract : This "magnetism‐optogenetic" system, which effectively combines the wireless magnetic regulation with the high sensitivity of optogenetics, used a magnetic field to drive mechanoluminescent materials to generate green light, thus activating hippocampal‐related neural responses and further regulating the movement behavior of rats. This new magnetism‐optogenetic system will provide an excellent reference for wireless and highly sensitive neuromodulation.